Case Report: Persistent residual shunt after a first percutaneous PFO closure followed by minimally invasive surgical failure: third time is a charm - Onorato, Eustaquio M.; Alamanni, Francesco; Monizzi, Giovanni; Mastrangelo, Angelo; Bartorelli, Antonio Luca (Frontiers in Cardiovascular Medicine, 2024)
Background Even though the optimal management of a moderate or large residual shunt following patent foramen ovale (PFO) closure is open to question, recent data confirmed that it is associated with an increased risk of stroke recurrence. Case summary A 48-year-old woman, a migraineur with visual aura, was diagnosed with a PFO associated with a huge multifenestrated atrial septal aneurysm (mfASA) and a moderate right-to-left shunt, detectable only after a Valsalva maneuver on contrast-transthoracic echocardiography. Brain magnetic resonance imaging showed a 1-mm silent white matter lesion in the right frontal lobe. Although the indication was not supported by guidelines, a transcatheter PFO closure was performed at another center with implantation of a large, equally sized, double-disc device (Figulla UNI 33/33 mm). At 6-month follow-up, a 2D/3D transesophageal echocardiography (TEE) color Doppler showed incorrect orientation of the device, which was not parallel to the interatrial septum, with two discs failing to capture the aortic muscular rim and partially protruding in the right atrium; furthermore, a 4 mm × 7 mm ASA fenestration was documented with a residual bidirectional shunt. Thereafter, the same team performed a minimally invasive cardiac surgery under femoro-femoral cardiopulmonary bypass; however, the procedure proved ineffective and was complicated by postoperative pericarditis with pericardial effusion, requiring further rehospitalization 1 month later due to persistent pericarditis, bilateral pleuritis, phrenic nerve palsy, and atrial flutter, which was treated with amiodarone. The patient asked for a second opinion, and our multidisciplinary heart team decided to offer a percutaneous redo intervention. An uneventful implantation of a regular PFO occluder (Figulla Flex II 16/18 mm) across the septal defect was performed successfully. Twelve-month follow-up with 2D TTE color Doppler and contrast transcranial Doppler showed correct position and good interaction between the two devices, with no residual shunt. Discussion In addition to the incorrect indication for PFO closure and the failure of minimally invasive surgery, the procedural mishap in this case could have been due to the inappropriate implantation of the first large device within the tunnel. It would have been better to deploy the same large device in the most central fenestration, covering the PFO and a greater part of the remaining mfASA at the same time.